2015
DOI: 10.1016/j.jconrel.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of tobramycin polymeric nanoparticles for Pseudomonas aeruginosa infections in cystic fibrosis: Formulation, characterisation and functionalisation with dornase alfa (DNase)

Abstract: Inhaled antibiotics, such as tobramycin, for the treatment of Pseudomonas aeruginosa pulmonary infections are associated with the increase in life expectancy seen in cystic fibrosis (CF) patients over recent years. However, the effectiveness of this aminoglycoside is still limited by its inability to penetrate the thick DNA-rich mucus in the lungs of these patients, leading to low antibiotic exposure to resident bacteria. In this study, we created novel polymeric nanoparticle (NP) delivery vehicles for tobramy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 41 publications
2
81
0
Order By: Relevance
“…Nanoparticles functionalized with biofilm EPS matrix-digesting enzymes (DNase) and loaded with ciprofloxacin eradicated established P. aeruginosa biofilms without cytotoxicity against macrophages 49 . Likewise, tobramycin alginate-chitosan nanoparticles functionalised by conjugation to dornase alfa (DNase) demonstrated better biofilm penetration and DNA degradation in sputum from patient with cystic fibrosis and increased protection against bacteria in an invertebrate infection model 148 . Furthermore, nanoparticles that were designed to release and activate NO in situ had antifungal and antibacterial effects, inhibited biofilm formation and promoted the degradation of the EPS matrix in vitro and in vivo 149,150 .…”
Section: The Promise Of New Technologiesmentioning
confidence: 99%
“…Nanoparticles functionalized with biofilm EPS matrix-digesting enzymes (DNase) and loaded with ciprofloxacin eradicated established P. aeruginosa biofilms without cytotoxicity against macrophages 49 . Likewise, tobramycin alginate-chitosan nanoparticles functionalised by conjugation to dornase alfa (DNase) demonstrated better biofilm penetration and DNA degradation in sputum from patient with cystic fibrosis and increased protection against bacteria in an invertebrate infection model 148 . Furthermore, nanoparticles that were designed to release and activate NO in situ had antifungal and antibacterial effects, inhibited biofilm formation and promoted the degradation of the EPS matrix in vitro and in vivo 149,150 .…”
Section: The Promise Of New Technologiesmentioning
confidence: 99%
“…There have been increasing reports on the incorporation of antibiotics into nanocomposites and nanodelivery systems. Recently, DNase tobramycin polymeric nanoparticles have shown improved drug delivery and antimicrobial activity against P. aeruginosa [212]. Despite progress being made, nanoantimicrobial agents are not yet used in human clinical applications.…”
Section: Nanoantimicrobials and Nanoantibioticsmentioning
confidence: 99%
“…Discussion on some of the newer antibiotics at different developmental and approval stages can be located elsewhere [216,217]. Numerous studies reported the effectiveness of nanoantimicrobial agents against Gram-negative bacteria including P. aeruginosa [212,[218][219][220][221][222][223][224]. …”
Section: Nanoantimicrobials and Nanoantibioticsmentioning
confidence: 99%
“…One possible approach is the use of specific PEMs that allow versatile and tunable release of drugs like antibacterial substances and make them additionally attractive as coatings for implantable devices [62].…”
Section: Antibacterial Pems With Pharmacological Functionmentioning
confidence: 99%